Hate crime in India: understanding nuanced discrimination against North-Eastern population - Bajpai, G. S. (Springer Nature, 2023)
This book investigates perceptions against the people of north-east India, and why such prejudicial attitude exists. It subsequently quantifies and develops measures to counter such stereotypes and affiliated violence. This research examines the north-east Indian populations and the general Indian populations understanding of hate crime against the north-eastern population in metropolitan cities of India, both in concept and in perpetration. Further, it evaluates the existing constitutional and statutory provisions in India to determine if the proposed legislation and provisions are sufficient with regards to hate crime against north-eastern people of India. Drawing on empirical research addressing racial hate crimes in Delhi, Mumbai, Bengaluru, Chennai, Hyderabad and Pune, this books case studies provide a qualitative dive to the problem and offer experiential analysis in order to curate preventive measures. This book is ideal for scholars, researchers, teachers and students interested in hate crime, racial violence, minority struggles, victimology, and law